Knowledge, Attitude and Obstacles of Colorectal Cancer Screening in Primary Health Care in Bali, Indonesia - Mariadi, I Ketut; Somayana, Gde; Sindhughosa, Dwijo Anargha (The Indonesian Society for Digestive Endoscopy, 2023)
Background: The knowledge of CRC and its screening methods of healthcare workers is the bedrock of CRC early detection particularly in countries lacking national screening programs. Unknown factors influencing colorectal cancer early detection program implementation. We aimed to evaluate the knowledge and attitudes of primary health care (PHC) provider regarding CRC screening and identify the barriers associated with the screening plan.Methods: A cross-sectional study was conducted among PHC physicians and nurses in public primary health care centers in Bali, Indonesia. A 44-item self-administered questionnaire was used to assess the knowledge, attitude and practice of CRC screening. The questionnaire was spread using google form. Results: Two hundred and five respondents have participated in this study. The average duration of doing practice in PHC is 6.6 years. In knowledge of CRC, 50.2% of them have good knowledge, and there is no difference between PCPs vs nurses (51.9% vs 47.3%; p=0.53). In attitude toward CRC screening, 58.5% out of the have good attitude, and there is no difference between PCPs vs nurses (60.3% vs 55.4%; p=0.50). The barriers of the screening was divided into two areas, a barrier from the health care system and patients. There was no association between knowledge and attitude towards CRC screening (p=0.63).Conclusion: The majority of health workers' knowledge and attitudes toward CRC screening were in the